Experimental and Simulation Evaluation of Temperature and Air Flow in Tunnel-Type Dryers: Preliminary Study - Akhyar Akhyar; Darwin Harun; Muhammad Robby; Muhammad Ilham Maulana; Ahmad Farhan (Politeknik Negeri Lhokseumawe, 2022)
Solar energy is a source of electricity for various industrial applications, such as water heating and drying. In the drying application, energy is transferred from one point to another due to the temperature difference of the sample material. This promoted the significant use of dryers by both farmers and fishermen to preserve their harvest or catch. However, there are several problems associated with the open system drying, such as inconsistent drying duration, dirt, fungus contamination, and rain. Therefore, this research aims to analyze heat transfer and airflow in the drying chamber of a tunnel-type application, using experimental and computational simulations. The general applied methods encompassed measuring the dryer’s in situ temperature, modeling the heat transfer, and analyzing the computational fluid dynamics(CFD) simulations for the airflow in the drying chamber between 08:00-15:30 GMT+7 (February 9, 2021). The temperature and airflow simulations of the system were analyzed and validated without a load of dried materials. Based on the measurement results, the minimum inlet and outlet temperatures occurred at 30.2oC (08.00 GMT+7) and 24ºC, similar to the simulation at 31.2ºC (08:00 GMT+7). Meanwhile, the maximum inlet and outlet temperatures were evaluated at 45.7 and 39ºC, with an outlet simulation temperature of 41.5ºC (12:00 GMT+7). These overall results indicated that the temperature values did not vary extensively. Therefore, the applied drying system is best suitable for post-harvest agricultural, forestry, and marine drying applications.